Chronic radiation exposure at Chernobyl shows no effect on genetic diversity in the freshwater crustacean, Asellus aquaticus thirty years on. Issue 18 (24th August 2019) - Fuller, Neil; Ford, Alex T.; Lerebours, Adélaïde; Gudkov, Dmitri I.; Nagorskaya, Liubov L.; Smith, Jim T.
Abstract: Analysis of genetic diversity represents a fundamental component of ecological risk assessments in contaminated environments. Many studies have assessed the genetic implications of chronic radiation exposure at Chernobyl, generally recording an elevated genetic diversity and mutation rate in rodents, plants, and birds inhabiting contaminated areas. Only limited studies have considered genetic diversity in aquatic biota at Chernobyl, despite the large number of freshwater systems where elevated dose rates will persist for many years. Consequently, the present study aimed to assess the effects of chronic radiation exposure on genetic diversity in the freshwater crustacean, Asellus aquaticus, using a genome‐wide SNP approach (Genotyping‐by‐sequencing). It was hypothesized that genetic diversity in A. aquaticus would be positively correlated with dose rate. A. aquaticus was collected from six lakes in Belarus and the Ukraine ranging in dose rate from 0.064 to 27.1 µGy/hr. Genotyping‐by‐sequencing analysis was performed on 74 individuals. A significant relationship between geographical distance and genetic differentiation confirmed the Isolation‐by‐Distance model. Conversely, no significant relationship between dose rate and genetic differentiation suggested no effect of the contamination gradient on genetic differentiation between populations. No significant relationship between five measures of genetic diversity and dose rate was recorded, suggesting that radiation exposure has not significantly influenced genetic diversity in A. aquaticus at Chernobyl. This is the first study to adopt a genome‐wide SNP approach to assess the impacts of environmental radiation exposure on biota. These findings are fundamental to understanding the long‐term success of aquatic populations in contaminated environments at Chernobyl and Fukushima. Abstract : This study utilized a genotyping by sequencing method to provide a novel assessment of the impacts of chronic radiation exposure at Chernobyl on a freshwater crustacean. No significant impact of over 30 years of radiation exposure on genetic variation was recorded. These findings are fundamental to understanding the long‐term success of aquatic populations in contaminated environments at Chernobyl and Fukushima.